PENGARUH KONSELING KELOMPOK DALAM MEREDUKSI PERILAKU PROKRASTINASI AKADEMIK SISWA KELAS XI DI SMA NEGERI 2 INDRALAYA UTARA - Prabowo, Yoga Dwi; Dewi, Ratna Sari (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
Academic procrastination is a behavior of delaying task completion, which serves as one of the obstacles to students’ academic achievement. This study aims to determine the effectiveness of group counseling services in reducing academic procrastination among 11th-grade students at SMA Negeri 2 Indralaya Utara. The research employed an experimental method with a One Group Pretest-Posttest Design, involving 10 students as research subjects. The instrument used was a scale of academic procrastination that had been tested for validity and reliability. Data were analyzed using descriptive statistics and paired sample t-test with the help of SPSS version 16. The results showed a significant difference between pretest and posttest scores, with a significance value of 0.000 < 0.05. The average score decreased to 64.70, indicating a reduction in procrastination behavior. Therefore, it can be concluded that group counseling services are effective in helping students reduce academic task delay behavior.